Fault Attacks against a Cellular Automata Based Stream Cipher - Carrijo, José; Nascimento, Anderson C. A.; Tonicelli, Rafael; Alves, Vinícius de Morais (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2011: Anais do XI Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2011)
This paper presents fault attacks against a cellular automata based stream cipher. A fault attack assumes that the adversary is able to physically operate the cryptographic device and insert some errors into it. As a consequence, the adversary can induce faulty results into the device and use them to recover the stored secret key. By using this approach we provide extremely efficient and practical cryptanalytic methods: by injecting n/2 + n 2 /32 faults we recover the n-bit secret key from a stream cipher based on cellular automaton rule 30. To the best of our knowledge this is the first application of fault attacks against cellular automata based stream ciphers.